PROFIL KONSUMEN DAN PESAING PADA â€œFACTORY BAKERYâ€ - Ramdhan ., Salam; Leonardus R. Rengkung; Theodora M. Katiandagho; Charles R. Ngangi (Sam Ratulangi University, 2015)
The purpose of this study was to describe the profile of competitors and consumers in the Factory Bakery. This research was conducted at the Factory Bakery is located at Pogidon Street, Tuminting, Manado. The collection of data carried out for three months, from June 2015 to Agustus 2015. The primary data in this study were taken two ways to measure the variables of consumers by asking directly to consumers for six days, whereas for measuring competitors by asking directly to the owner of the business. The secondary data is obtained through agencies associated with this research. Sampling was done by accidental sampling technique, that where the samples taken are all consumer who are buying the products of Factory Bakery. Analysis of the data used is descriptive. The results show that the segmentation is done by Factory bakery based on gender, occupation, type of education, age, and region of origin has been proved that the Factory of Bakery has understood the needs and desires of consumers well. While the motivation was given in terms of price, service, location, facilities, flavors and shapes and variations to make the consumer has been satisfied with the Factory Bakery. Competitors that exist around the Factory Bakery can make an effort Factory Bakery threatened with various advantages Factory Bakery competitors but could still survive in competition with emphasis on quality products owned.